Does FinTech change the market power of traditional banks in China? - Qi, Hanying; Yang, Keng; Wang, Weijia (Journal of Business Economics and Management, 2022)
This study assesses the impact of the development of financial technology (FinTech) on the market power of traditional banks. We analyze the relationship between FinTech companies and traditional banks based on the barriers-to-entry theory, and verify the resulting hypothesis by using panel data from 155 Chinese commercial banks from 2013–2018. The benchmark results show that FinTech has a significant U-shaped effect on the market power of banks. Furthermore, the U-shaped effects remain robust when we focus on the technology and business innovation channels that affect banks. These effects vary across banks with different ownership structures and business segments. Specifically, municipal commercial banks are more likely to be influenced by business innovation than by technological innovation. By contrast, state-owned banks have advantages in using technological innovation to reacquire market power through loan services. Private banks, meanwhile, struggle to acquire any market power under intense competition from FinTech companies. Given that the FinTech may enable some banks overly dominate the banking industry at certain development stages, regulators and practitioners need to prevent monopoly-related problems and promote the digital transformation of small and medium-sized banks.First published online 30 August 2022